Enhancing Womenpreneur Capabilities Through Innovation Development: Crossing The Chasm Framework - Indrawati, Rosita; Dewi, Liliana (Dinasti Publisher, 2025)
This study examines challenges faced by Indonesian womenpreneurs in innovation development and capability enhancement. Using a quantitative approach with Partial Least Square-Structural Equation Modelling (PLS-SEM), data were collected from 100 women entrepreneurs in Indonesia's tourism sector MSMEs. Results indicate that innovative behavior and entrepreneurial competencies significantly influence innovation development, which positively impacts womenpreneur success through innovation implementation. However, skill development programs showed no significant effect on innovation development. The findings emphasize the critical role of innovative behavior and entrepreneurial competencies in driving innovation development and subsequent business success among women entrepreneurs.